SYSTEMIC APPROACH TO TRANSLATION: EXPERIMENTAL RESEARCH - Oleksandr Rebrii (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2017)
The article deals with the problem of translation as a system and analysis of its systemic features in both structuralist and process-oriented paradigms. In its structuralist dimension, systemic nature of translation is revealed through that of a text (as the main object of translation analysis) and language (as a source of its means). In its process-oriented dimension, translation is revealed in translator's systemic thinking. Researching the specifics of systemic thinking as a cognitive activity requires a new methodology. The article proposes the exploration into translator's decision-making on the basis of experimental method of autointrospection, which is defined as exteriorisation of translator's considerations as to different aspects of the activities he or she is being engaged in. For this purpose, the eccentric tale by S. Milligan was translated and notes were taken as to the specifics of overcoming selected translation difficulties of the lexical level (proper names, onomatopoeias, culturally-bound lexemes, nonce words, and puns). Special attention was given to formulating a general strategy of translation of the text in general and local strategies for reproduction of the selected lexical items. The research allowed to draw some conclusions as to: correlation between structuralist and process-oriented vision of translation as a system; ways and methods of correlating methods of systemic translating lexical items both within their categories and among these categories on the general textual level. Systemic thinking is thus presented as a skill whose development is the essential part of translators' professional training.